A review of the Oriental Copelatus latipes complex, with the description of two new species (Coleoptera: Dytiscidae: Copelatinae) - Hájek, Jiří; Sheth, Sayali D. (Zootaxa, 2024)
The Copelatus latipes species complex is introduced for Oriental species of Copelatus Erichson, 1832 belonging to the C. irinus group and characterised by the presence of processes on the ventral side of the median lobe of the aedeagus, forming a “beak-shaped” structure. The complex comprises six species, including two newly described taxa: Copelatus bezdeki Sheth, Ghate & Hájek, 2018 (India), C. brivioi Rocchi, 1976 (Bangladesh, India, Nepal), C. kopetzi sp. nov. (Nepal), C. lanxangensis sp. nov. (Laos), C. latipes Sharp, 1882 (Cambodia, Indonesia, Laos, Malaysia) and C. schereri Wewalka, 1981 (India, Sri Lanka). All species are diagnosed, and their habitus and male genitalia are illustrated.